2015
DOI: 10.1590/1983-084x/13_008
|View full text |Cite
|
Sign up to set email alerts
|

Biomassa e teor de óleo essencial em Aloysia triphylla (l'hérit) Britton submetida a diferentes níveis de reposição hídrica e à variação sazonal das condições ambientais

Abstract: RESUMO:A variação nos elementos meteorológicos ao longo do ano, configurando as quatro estações, proporciona diferentes condições de crescimento e desenvolvimento das plantas, alterando o metabolismo e a constituição dos tecidos vegetais. Assim, o presente trabalho teve o objetivo de determinar a influência da sazonalidade em parâmetros fenométricos e na produção de óleo essencial em Aloysia triphylla (L'Hérit) Britton, submetida a diferentes níveis de reposição hídrica cultivada em ambiente protegido. As aval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Britton (Verbenaceae) is a herbal species native to South America, also cultivated in Southern Europe and North Africa (Valentão, Fernandes, Carvalho, Andrade, Seabra & Bastos 2002;Paulus, Valmorbida, Toffoli, Nava & Paulus 2013). It is rich in highly volatile compounds that have aromatic and sedative properties (Schwerz, Caron, Manfron, Schmidt & Elli 2015). The commercial importance of the essential oil of A. triphylla (EOAT) also depends on its two main components, geranial and neral, that are directly related to its functional properties (Tabatabaie & Nazari 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Britton (Verbenaceae) is a herbal species native to South America, also cultivated in Southern Europe and North Africa (Valentão, Fernandes, Carvalho, Andrade, Seabra & Bastos 2002;Paulus, Valmorbida, Toffoli, Nava & Paulus 2013). It is rich in highly volatile compounds that have aromatic and sedative properties (Schwerz, Caron, Manfron, Schmidt & Elli 2015). The commercial importance of the essential oil of A. triphylla (EOAT) also depends on its two main components, geranial and neral, that are directly related to its functional properties (Tabatabaie & Nazari 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This factor was observed in the rainy season, during which the highest rainfall indices were registered (Figure 1). Schwerz et al (2015) studied the biomass yield of Aloysia triphylla and verified the effect of the seasonal variation in leaf dry weight yield (g plant -1 ), with the highest yield observed in plants collected in November. The season also significantly affected the dry weight yield of citronella (Cymbopogon winterianus Jowitt), which presented higher yield in the dry season than in the rainy season (BLANK et al, 2007).…”
Section: Resultsmentioning
confidence: 92%
“…Ferreira et al (2016) reported seasonal variation due to climatic conditions as being a more limiting factor than nitrogen fertilization in sweet basil yield (Ocimum basilicum). Seasonality also affected biomass yield and essential oil concentration of Mentha arvensis L. and Aloysia triphylla (CHAGAS et al, 2011;SCHWERZ et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Extraction of the essential oil was accomplished through distillation in a Clevenger (Farmacopeia Brasileira, 2000). The plant material was placed in a 5,000-mL volumetric Temporal and spatial variation in the composition, relative proportion, and scale of each component in essential oils is caused by seasonal and daily changes (Chagas et al, 2011;Schwerz et al, 2015). Several reports (Schwerz et al, 2015;Prochnow et al, 2017;Schmidt et al, 2017) have discussed the variation in biomass, content, and composition of A. triphylla essential oil, attributing them to the climatic factors.…”
Section: Extraction Of Essential Oilmentioning
confidence: 99%